Green Agriculture: a Review of the Application of Micro- and Macroalgae and Their Impact on Crop Production on Soil Quality - Kholssi, Rajaa; Lougraimzi, Hanane; Grina, Fatiha; Lorentz, Juliana F.; Silva, Iosody; Castaño-Sánchez, Omar; Marks, Evan A. N. (Journal of soil science and plant nutrition, 2022)
Due to intensive agricultural practices, agricultural lands are subject to continuous degradation. Agricultural productivity depends to a great degree on soil characteristics — soil is the substrate which when managed properly can support plant growth, but when abused requires additional inputs. Research is increasingly focused on the development of new non-synthetic and non-fossil-based products having less impact on the environment and health. In this context, the use of algae biomass (macro and micro) has been widely researched as a fertilizer for agricultural production as a “green economy” alternative product. Currently, the production of marine algae far outstrips the production of microalgae and its main use is for food consumption and some industrial applications. The cost of production is also variable, as marine algae are usually cultivated in integrated multitrophic aquaculture systems. The production of microalgae involves many variables, among them the species, the culture medium, obtaining process, final application, etc. and, based on these, its production cost is estimated. Some researchers point out that the use of simplified technology and increased production capacity tend to reduce operating costs within the ideal photosynthetic yield. This review sought to highlight the importance of algae and their extracts as natural biofertilizers and biostimulants, as well as the mechanisms of action and the possible relationship of these organisms with cultivated plants. Highlights • Macroalgae are potentially highly advantageous for sustainable agriculture. • Microalgae can serve as biofertilizers or biostimulants. • Algal extracts promote plant growth and nutrients uptake. • The economic viability of biofertilizer production must be addressed.